Suicide genes: monitoring cells in patients with a safety switch - Eissenberg, Linda G.; Rettig, Michael; Dehdashti, Farrokh; Piwnica-Worms, David; DiPersio, John F. (Frontiers in Pharmacology, 2014)
Clinical trials increasingly incorporate suicide genes either as direct lytic agents for tumors or as safety switches in therapies based on genetically modified cells. Suicide genes can also be used as non-invasive reporters to monitor the biological consequences of administering genetically modified cells to patients and gather information relevant to patient safety. These genes can monitor therapeutic outcomes addressable by early clinical intervention. As an example, our recent clinical trial used 18F-9-(4-fluoro-3-hydroxymethylbutyl)guanine (18FHBG) and PET/CT scans to follow T cells transduced with herpes simplex virus thymidine kinase (TK) after administration to patients. Guided by preclinical data we ultimately hope to discern whether a particular pattern of transduced T cell migration within patients reflects early development of Graft vs. Host Disease (GvHD). Current difficulties in terms of choice of suicide gene, biodistribution of radiolabeled tracers in humans versus animal models, and threshold levels of genetically modified cells needed for detection by PET/CT are discussed. As alternative suicide genes are developed, additional radiolabel probes suitable for imaging in patients should be considered.